2019
DOI: 10.1111/iju.14077
|View full text |Cite
|
Sign up to set email alerts
|

Short‐term impact of androgen deprivation therapy on bone strength in castration‐sensitive prostate cancer

Abstract: Objectives To prospectively evaluate changes in bone quality and bone mineral density after androgen deprivation therapy in castration‐sensitive prostate cancer. Methods A total of 32 patients with castration‐sensitive prostate cancer who were scheduled for androgen deprivation therapy for >12 months were included. The bone mineral density of the femoral neck and lumbar spine was evaluated before, and 6 and 12 months after androgen deprivation therapy. Bone metabolic (serum undercarboxylated osteocalcin, tartr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…P1NP was not affected in our study. Discrepancies have been observed, with both unaltered (6) and increased (38) P1NP levels being reported following ADT. Timing could play a role, as others have described a decrease in serum P1NP after 4 weeks of ADT in healthy men, which normalized again by 12 weeks (37).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…P1NP was not affected in our study. Discrepancies have been observed, with both unaltered (6) and increased (38) P1NP levels being reported following ADT. Timing could play a role, as others have described a decrease in serum P1NP after 4 weeks of ADT in healthy men, which normalized again by 12 weeks (37).…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that male hypogonadism is associated with bone loss. Accordingly, in prostate cancer patients androgen deprivation therapy (ADT) induces bone loss, thereby increasing the risk for osteoporosis and fractures (2)(3)(4)(5)(6)(7)(8)(9). However, in case of metastatic prostate cancer the impact of ADT per se on bone homeostasis could be obscured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, other modes of treatment are sought after cancer advances further. It has also been shown that ADT can cause a significant decrease in bone mineral density and is one of the major side effects of ADT [37] …”
Section: Treatment Of Pcamentioning
confidence: 99%
“…Although the incidence of prostate cancer in Asian countries, including Japan, is lower than in North America and Europe, it is expected that it will rapidly increase in the future as the population ages [1][2][3]. Most prostate cancer treatments, mainly androgen deprivation therapy (ADT), lead to cancer treatment-induced bone loss (CTIBL) and increase the risk of fracture [4][5][6][7][8], which is greatly related to the patient's quality of life (QOL). Identifying the characteristics of patients at risk of fracture before the initiation of cancer treatment is becoming more important for maintaining QOL during and after cancer treatment in elderly patients.…”
Section: Introductionmentioning
confidence: 99%